PENGARUH SUKU BUNGA RIIL, PRODUK DOMESTIK BRUTO (PDB) DAN KETERBUKAAN KEUANGAN (DEGREE OF FINANCIAL) TERHADAP INVESTASI PMA DI INDONESIA TAHUN 2000-2013 - Novita '; Anthony Mayes; Darmayuda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the influence of the real interest rate, Gross Domestic Product (GDP) and Financial Openness (Degree Of Financial) to the changes of Foreign Direct Investment (FDI) in Indonesia period of 2000-2013. The data used in this study is the data times series from years 2000-2013 are sourced from Financial Statements of Bank Indonesia (BI), The Central Statistics Agency (BPS) and the Asian Develompment Bank (ADB). This study uses quantitative methods and analyzed using the multiple linear regression analysis will use the t-statistic to test the partial coefficient and F-Statitisk to test the effect of jointly using Eviews 3.0 applications. Based on the results of multiple regression analysis, Simultaneously independent variable effect simultaneously with a significance level of 0.05% to Foreign Direct Investment (FDI). Given also the coefficient of determination (0.680164) means the influence of independent variables on the dependent variable of 68.0164% and the remaining 31.98% is affected by factors beyondin this riset. Partial known that GDP and Financial Openness (Degree Of Financial) significant positive effect on Foreign Direct Investment (FDI) in Indonesia. While the real interest rate negative and not significant to Foreign Direct Investment (FDI) in Indonesia. Then dependent variable more effect to Foreign Direct Investment (FDI) is Gross Domestic Product (GDP) and Financial Openness (Degree Of Financial).Keywords : Foreign Direct Investment, Real Interest Rate, Gross Domestic Product (GDP) and Financial Openness (Degree Of Financial)